2002
DOI: 10.1248/jhs.48.7
|View full text |Cite
|
Sign up to set email alerts
|

Trans Fatty Acids: Properties, Benefits and Risks.

Abstract: Trans fatty acids have several beneficial aspects for processed foods owing to their characteristic structures. These very characteristic structures, in turn, have been suspected to be associated with the possibility that trans fatty acids affect the development of several health problems, including coronary heart disease, and fetal and infant neurodevelopment and growth, and childhood allergies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
37
0
20

Year Published

2005
2005
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(58 citation statements)
references
References 51 publications
1
37
0
20
Order By: Relevance
“…TFA in food has three major sources, partial hydrogenation of fat, high-temperature processing of edible oils, and the natural occurrence in ruminant meat and dairy products (Majøs 2005). Because of the negative health effects of TFA, they have recently received increasing attention and are considered to be even more detrimental than the saturated ones (Semma 2002). Epidemiological studies have shown a strong positive association between TFA intake and cardiovascular disease (CVD) risk (Ghafoorunissa 2008).…”
Section: Introductionmentioning
confidence: 99%
“…TFA in food has three major sources, partial hydrogenation of fat, high-temperature processing of edible oils, and the natural occurrence in ruminant meat and dairy products (Majøs 2005). Because of the negative health effects of TFA, they have recently received increasing attention and are considered to be even more detrimental than the saturated ones (Semma 2002). Epidemiological studies have shown a strong positive association between TFA intake and cardiovascular disease (CVD) risk (Ghafoorunissa 2008).…”
Section: Introductionmentioning
confidence: 99%
“…When a control fat or oil is unknown, the fatty acid composition (including the degree of unsaturation) and the varying chain lengths are useful for establishing the distinction between liquid oils and solid fats; the classification into drying, semi-drying, and nondrying oils; and the discrimination of types of fats and oils. Fatty acid composition is frequently analyzed by gas chromatography (GC) [4][5][6][7][8][9][10] and gas chromatography-mass spectrometry (GC-MS) [1][2][3][11][12][13][14] of saponifiables 1,2,4,5,11-13 for their classification, or for the discrimination of fats and oils. When fats and oils are saponified, saponifiables are obtained in the form of fatty acid salts, such as potassium salts in an aqueous layer.…”
Section: Introductionmentioning
confidence: 99%
“…4 -------C10:0 171 2.8 ----trace --C12:0 199 1.5 -------C14:0 227 2.7 -------C14:1 225 trace trace ---1.3 --C15:0 241 2.5 -------C15:1 239 0.8 -------C16:0 255 Saponification of fats and oils for sample preparation Samples of fats and oils (approximately 0.2 g) were saponified with 0.5 M potassium hydroixde-ethanol solution (3 mL). 4,5,[11][12][13]22,23 The solution was heated for 1 h at 70˚C. After saponification, the solution was divided into two samples for GC-MS and ESI-MS analyses.…”
Section: Introductionmentioning
confidence: 99%
“…Some fatty acids have one or more double bonds in the trans configuration: these are the so-called trans fatty acids (TFAs) (Fritsche & Steinhart 1998). TFAs are present in variable amounts in a wide range of foods, including most foods made with partially hydrogenated oils such as baked goods and fried foods, and some margarine products (Semma 2002). TFAs content varies considerably among foods, reflecting, the differences in the fats and oils used in the manufacturing or preparation processes (Innis et al 1999).…”
mentioning
confidence: 99%